(untitled) (Research, Society and Development, 2022)
Third molar extraction is a frequently performed dental procedure and is associated with postoperative complications such as swelling, trismus and pain, in addition to generating anxiety for patients. These complications can impact on quality of life, which motivated dentists to seek alternatives, such as the use of acupuncture, as it has shown good results over the years in different health areas. Therefore, the objective of the present study was to carry out a literature review to verify the effect of acupuncture on the postoperative symptoms generated by third molar surgeries. The literature review was performed in the following electronic databases: MEDLINE via Pubmed, Lilacs e BBO, Portal de Periódicos Capes/MEC and Google Scholar. The effectiveness of acupuncture was observed due to anti-inflammatory, anxiolytic and myorelaxant action, promoting reduction of postoperative pain, edema, trismus and anxiety. It promotes general balance, and not just the treatment of the affected region, favoring homeostasis, in addition to helping to reduce anesthetics used during surgery and postoperative analgesics. It can be performed with the application of needles, laser and seeds in the acupoints present in the body and can also be performed in the ear, which favors the application in the dental office itself. Acupuncture can be considered a great ally to dental practice due to the extremely satisfactory results in the control of inflammatory events and anxiety. However, it is necessary to carry out more research on the subject, especially the development of randomized clinical trials, for a better scientific basis and greater applicability in the dental field.